EUROPEJSKA WSPÓLNOTA WĘGLA I STALI A SUWERENNOŚĆ PAŃSTWA CZŁONKOWSKIEGO. ASPEKT INSTYTUCJONALNO-DOKTRYNALNY - Madeja, Andrzej (Zeszyty Prawnicze, 2016)
EUROPEAN COAL AND STEEL COMMUNITY AND THE MEMBER-STATE’S SOVEREIGNTY. INSTITUTIONAL DOCTRINE ASPECT Summary Presented paper deals with the notion of sovereignty incorporated in the institutional solutions of the European Coal and Steel Community. The analysis is performed with a use of measures characteristic for institutional system research, but its main purpose is to reconstruct the vision of sovereignty born by drafters of the Treaty of Paris. Therefore author thoroughly ponders several institutional elements of the Community that are of crucial meaning for the problem posed in the title, such as: goal and scope of Community’s activity, competences and their distribution between organs, modes of taking decisions and voting procedures, character of acts adopted by organs, and financial aspects of Community. The main argument of the article is that six Member-States retained so called “competence of competences”, which is a legal counterpart of rather political term of sovereignty. Concluding and ratifying the Treaty states freely and voluntarily self-limited the scope of latitude in exercising their competences, simultaneously transferring a bundle of them to the Community. Handed over competences as well as forms of their exercise were meticulously determined in the Treaty. That’s why imprecise and inaccurate opinions of “surrender of sovereignty” are misleading. Despite similarities to federal system the first Community wasn’t in possession of entirely self-controlled competences that became once and for all detached from the national governments’ and parliaments’ powers. From perspective of the state’s sovereignty the new Community represented a peculiar form of a confederacy based on interstate bonds, sometimes called an “economic federation”.